P–454 Oocyte vitrification for fertility preservation in women with benign gynecological disease: French national clinical guidelines with a modified Delphi consensus process. (6th August 2021) - Courbière, B; Roux, E L; Mathie. D'Argent, E; Torre, A; Patrat, C; Poncelet, C; Montagut, J; Gremeau, A S; Creux, H; Peigne, M; Chavanaz-Lacheray, I; Dirian, L; et al.
Abstract: Study question: Is there consensual clinical practices about fertility preservation (FP) for benign gynecological diseases BGD)? Summary answer: A consensus study using the modified Delphi method identified 28 consensual practices concerning oocyte vitrification for fertility preservation in women with benign gynecological disease. What is known already: Clinical Practical international guidelines are still published in oncology for offering standardized information and care for adults and children with cancer. Recently, the ESHRE Female Fertility Preservation Guideline Development Group published recommendations for healthcare professionals involved in fertility preservation for post-pubertal women and transgender adolescents and young adults. However, benign gynecological indications weren't distinctly individualized of malignant conditions. There's a lack of large cohort studies assessing the risks and outcome of FP for benign gynecological diseases. Healthcare professionals need consensus for defining the "good" indications of FP for benign gynecological diseases that could impair fertility. Study design, size, duration: A steering group composed by 14 healthcare professionals and a patient representative with lived experience of endometriosis identified 42 potential practices concerning fertility preservation for benign gynecological disease. Then, 114 key stakeholders including various healthcare professionals (n = 108) and patient representatives(n = 6) were asked to answer at two rounds of a modified Delphi via an online survey from February to September 2020. Participants/materials, setting, methods: Participants had to score 42 items for the first round and 31 for the second round using a nine-point Likert scale. These statements were distributed into five categories: Information to deliver to age-reproductive women with a BGD (n = 9), technical aspect of fertility preservation for BGD (n = 6), indications of FP for endometriosis (n = 13), indications of FP for none-endometriosis BGD (n = 10), idiopathic diminished ovarian reserve in the absence of gynecologic and endocrinologic diseases (n = 4). Main results and the role of chance: Survey response of stakeholders was 75% (86 out of 114) for the round 1 and 87% (75 out of 86) for the round 2. Consensus recommendations were achieved for 28 items, and no consensus between stakeholders was achieved in the remaining items. Stakeholders rated the importance of an age-specific information concerning the risk of diminished ovarian reserve after surgery and the necessity to inform about the benefice/ risk balance of oocyte vitrification, in particular about the chance of live-birth according to the age at the time of oocyte vitrification. They endorsed oocyte vitrification as the reference FP technique for those benign indications. Experts rejected to determine lower and upper age limits in women for fertility preservation. FP shouldn't be offered in rAFS stages I and II endometriosis without endometriomas. Limitations, reasons for caution: Experts were only French native speakers from France, and Belgium. It would have been interesting to conduct this survey with experts from other continents. Wider implications of the findings: At our knowledge, we present here the first guideline s focusing on FP in women with BGD, following a designed scientific Delphi procedure. These guidelines could be useful for gynecologists to better inform women with benign gynecological diseases about the indication or not to offer a FP procedure. Trial registration number: Not applicable